Keratinization and Muscular Variation in the Abdominal Esophagus of Rabbit and Guinea Pig - Noora Kadhim Sheriff; Bassim Abdullah Jassim (Academia Open, 2025)
Background: The esophagus exhibits species-specific structural adaptations related to diet and function, particularly in its abdominal segment. Method: Samples from adult rabbit and guinea pig esophagi were processed using routine histological techniques and stained with hematoxylin and eosin. Measurements of epithelial height and muscularis thickness were statistically analyzed (P ≤ 0.05). Results: Significant histomorphometric differences were observed between the two species in epithelial and muscular thickness, with the exception of the submucosal layer. Aims: To compare the histological architecture of the abdominal esophagus in adult rabbits and guinea pigs, focusing on epithelial keratinization and muscular organization. Findings: Both species showed keratinized stratified squamous epithelium, but the degree of keratinization and muscle layer arrangement varied. The rabbit showed partial keratinization and a thicker muscularis externa, while the guinea pig had full keratinization and complex muscular layering. Novelty: This study provides the first direct comparative analysis of the abdominal esophageal segment between these two rodent species, highlighting structural distinctions potentially linked to dietary habits. Impact: The findings offer valuable insights for veterinary anatomy, comparative histology, and may inform experimental models involving the gastrointestinal tract in small mammals. Highlights: Species Comparison: Highlights structural differences in the esophagus between rabbits and guinea pigs. Keratinization Pattern: Shows variation in epithelial keratinization linked to species-specific function. Veterinary Insight: Provides data useful for experimental and anatomical studies in small mammals. Keywords: Esophagus, Rabbit , Histology, Histochemical.